Pengaruh Digitalisasi Ekonomi terhadap Gaya Hidup Generasi Z (Studi Kasus pada Mahasiswa UIN K.H. Abdurrahman Wahid Pekalongan) - Nafisah Asnal Muna (Sahmiyya, 2023)
Economic digitalization affects the lifestyle of Z generation. Changes in the economic system that make it easier for users are often misused. The purpose of this study was to explain the effect of economic digitalization on the lifestyles of UIN K.H. students. Abdurrahman Wahid Pekalongan. This study uses a literature review approach that originates from books and journals related to the research topic. The data analysis used interview techniques. The results of this study indicate that economic digitization has an influence on the lifestyle of generation Z youth. The existence of economic digitalization has also changed the business world, business entities are utilizing technology to open online stores, commonly known as e-commerce. However, what is currently in the public spotlight is the use of online shopping through applications. This online shop platform has become a favorite use of people all over the world, especially Indonesia because it is easy to use along with access that can be observed easily according to the procedures of the platform. The rapid pace of information technology in this digitalization era will eventually result in consumptive societal behavior. The current consumption behavior of people in using online shops has increased quite high, especially consumption of fashion products. It is clear that the current modern era factor is the main attraction for people to follow because they do not want to be left behind with the others. Community behavior is not only determined by each individual, but also determined by the environment in which they live. In addition, society assumes that someone will be accepted in their environment if they follow the current lifestyle, currently online shops are incessant in meeting their daily needs.